Bactericidal Activity of the Combinations of Gentamicin with Clindamycin or Chloramphenicol Against Species of Escherichia coli and Bacteroides fragilis - Klastersky, Jean (1977)
The bactericidal activity of clindamycin, chloramphenicol, and gentamicin alone and of gentamicin plus clindamycin and gentamicin plus chloramphenicol was studied on 8 strains of Escherichia coli and 10 strains of Bacteroides fragilis isolated from clinical material. Gentamicin did not interfere with the activity of clindamycin or chloramphenicol against B. fragilis. The activity of gentamicin against E. coli was not influenced by clindamycin, but chloramphenicol suppressed the rapid bactericidal activity of gentamicin in seven out of eight strains of E. coli examined.